Legislation intervening strikes in Iceland 1985-2010; grounds for legal intervention - Friðrik Friðriksson; Gylfi Dalmann Aðalsteinsson (Icelandic Review of Politics & Administration, 2010)
Strike is a key weapon fortrade unions in order to achieve their demands. The right to strike was incorporated into the private sector by the Trade Unions and Industrial Disputes Act in 1938. Until 1976 there were significant restrictions on ther ights of civil servants to strike. The main objectives of the Trade Unions and Industrial Disputes Act is to establish peace in the labour market and to minimize the damage for the economy and society as a whole which can occur from industrial disputes. Despite the law, strikes have been frequent in Iceland. During the period 1985-2010 there have been 166 strikes and 1,187,411 working days lost. The right to strike is not unconditional. The right to strike is subjected to certain restrictions based on laws and is restricted by the proportionality principle. The paper examines the arguments and considerations underlying the statutory limitations that have been set on the right to strike. The legislature has intervened in industrial conflicts on a different occasions, i.e. before a strike has begun, from the first day of a strike or a long time has passed the dispute and preventing a industrial conflict when the parties involved are not likely to reach a settlement. From 1985 to 2010 Althingi has passed 12 laws banning strikes, three related to labor disputes concerning flight operations, five concerning fishermen, two laws were passed concerning public employees,one for dairy scientists, and finally one to prohibit work stoppages in general. Legislative reasons to industrial dispute can be divided into three parts. First, if the economic significance of the nations economy and stability in the labour market are at stake, second, if the overall interests of the industry are at stake and finally, if the statutory programs and their implementation in the public sector are at stake. The paper discusses the idea whether or not it is appropriate to establish a court of arbitration in order to solve difficult industrial disputes.